Next Steps for LGBTQ+ Engagement in WPS Practice in Ireland - Richardson, Alexandra; Hagen, Jamie J. (Political Science Association of Ireland (PSAI), 2025)
The Women, Peace, and Security (WPS) agenda has achieved significant recognition as a framework for promoting gender equality in conflict resolution and peacebuilding. However, the lived experiences of Lesbian, Gay, Bisexual, Transgender, and Queer (LGBTQ+) individuals remain largely marginalised, both in the conceptualisation, implementation, and operationalisation of this agenda. This exclusion perpetuates structural inequities and diminishes the transformative potential of WPS frameworks. Insights from our "Workshop on Queering the Women, Peace and Security Agenda" (6th December 2024) underscore the urgent need for the Government of Ireland, the Irish Defence Forces, UN Member States, and wider epistemic communities to adopt a more inclusive and nuanced approach. This submission synthesises findings from detailed notetaker reports, highlighting practical recommendations for UN Member States, future Irish WPS National Action Plans (NAPs), and Irish Defence Forces WPS Action Plans (APs), showcasing the opportunities for the integration of queer perspectives across the WPS pillars of Prevention, Protection, Participation, and Relief and Recovery.
PUBLISHED
Keywords: queer theory; gender; peace; Women, Peace and Security; United Nations; Ireland; LGBTQ inclusion; Inclusive Society; International Development; International Integration; Critical theory and Theology; International Rights; Northern Ireland Conflict; Peace Studies; Religion, Conflict and Peace